Hubungan Phantom Vibration Syndrome Terhadap Sleep Disorder dan Kondisi Stress - Ajeng Yeni Setianingrum (Jurnal Optimasi Sistem Industri, 2017)
Phantom vibration syndrome is a condition where a person would feel the sensation of vibration of a cell phone as if there were incoming notification but the fact is not. This research investigated the relationship between phantom vibration syndromes, sleep disorder and stress condition. Questionnaires were distributed to 120 participants with age range 18 to 23 years old. Data of participants showed that all of participants using a smart mobile phone and 24% of them have more than one cell phone. Time usage of cell phone is at least 1 hour. 23% of participants using a cell phone for social media activity, followed by 21% related to entertainment (music, video and games). The results showed a positive relationship between phantom vibration syndrome, sleep disorder and stress condition. Insomnia contributed a greater influence on stress condition. However, the phantom vibration syndrome is more directly affecting the sleep apnea compared to insomnia and stress condition. Therefore, the phantom vibration syndrome more affects stress condition indirectly, through sleep disorder (sleep apnea and insomnia). Consequently, phantom vibration syndrome has a strong relationship with stress condition at the time of the phantom vibration syndrome can cause sleep disorder.